2017
DOI: 10.1016/j.bbadis.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 has dual effects on the HMGB1 and NF-κB signalling pathways and is a potential therapeutic target for osteoarthritis

Abstract: Osteoarthritis (OA) has traditionally been defined as a non-inflammatory disease. Recently, many studies have demonstrated that OA also has an inflammatory component. BRD4, a member of the Bromodomain and Extra-Terminal Domain family, has emerged as an important regulator of some chronic inflammatory diseases. JQ1, an antagonist of BRD4, modulates transcription of several genes. Our study demonstrated that BRD4 is up-regulated in articular cartilage of OA. BRD4 inhibition attenuated the inflammation and catabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 61 publications
7
74
0
1
Order By: Relevance
“…30 Due to the critical role of BRD4 in inflammatory response in other cell types, 12,29 we explored the underlying mechanism of BRD4 inhibition on microglial activation in vitro. 17 In line with these observations, we found that BRD4 knockdown and JQ1 both up-regulated the level of IκBα and inhibited phosphorylation of p65, thus blocking the activation of the NF-κB signalling pathway. 12 In addition, BRD4 knockdown inhibits the NF-κB signalling pathway by promoting the level of IκBα and preventing phosphorylation of p65 in IL-1β-treated chondrocytes.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…30 Due to the critical role of BRD4 in inflammatory response in other cell types, 12,29 we explored the underlying mechanism of BRD4 inhibition on microglial activation in vitro. 17 In line with these observations, we found that BRD4 knockdown and JQ1 both up-regulated the level of IκBα and inhibited phosphorylation of p65, thus blocking the activation of the NF-κB signalling pathway. 12 In addition, BRD4 knockdown inhibits the NF-κB signalling pathway by promoting the level of IκBα and preventing phosphorylation of p65 in IL-1β-treated chondrocytes.…”
Section: Discussionsupporting
confidence: 85%
“…12,13 Under pathological conditions, the phosphorylation of p38 mitogen-activated protein kinase (MAPK), c-Jun N-terminal kinase (JNK) and extracellular signal regulated kinase (ERK) is markedly increased in microglia, which may lead to increased expression of pro-inflammatory phenotypes such as TNF-α, IL-1β, IL-6 and INOS. 17,18 In the present study, we found that BRD4 level was correlated with pro-inflammatory cytokines after SCI in rats. 15 BRD4 inhibition by JQ1 was demonstrated to attenuate LPS-induced expression of pro-inflammatory cytokines and suppressed inflammatory reactions in macrophages; 16 studies also showed that JQ1 negatively modulates inflammation in rheumatoid arthritis and osteoarthritis indicating that suppression of BRD4 might be a potential therapeutic method against inflammatory response in SCI.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Substantial evidence has revealed that pro‐inflammatory molecules contribute to aggrecan and collagen II degradation and pro‐inflammatory cytokine expression (Johnson et al, 2015; Kang et al, 2015; Molinos et al, 2015; Wang et al, 2017). In addition, BRD4 is upregulated in articular cartilage, and BRD4 inhibition prevents inflammation in osteoarthritis and synovial inflammation (Jiang et al, 2017; Xiao et al, 2016; Xu & Vakoc, 2014). Similarly, our data showed that TNF‐α induced the expression of BRD4 in NP cells, while BRD4 inhibition by JQ1 alleviated matrix degradation in NP cells.…”
Section: Discussionmentioning
confidence: 99%